CONTAST ERROR FROM THE PERCENTUAL OF FAT AND FAT MASS ANALYSED BY DIFFERENT MATHEMATICAL MODELS APPLYED TO PROFESSIONAL FOOT-BALL ATHLETES (Fiep Bulletin - online, 2015)
One of the areas which helps the performance in the sport is linked to the athletes morphologic aspects. In this way, the aim of this study was to analyze the Constant Error ( EC) of the percentual of fat and fat mass of 11 mathematical models which utilized anthropometrical measures in order to value the corporal density with 4 mathematical models which convert the corporal density in percentual of fat comparing them with a hydrostatic pratice (technique) (PH). The group of the studied athletes were constituted of 25 subjects professional athletes of foot-ball, with an average of age of 22,7 ± 4,4 years old. It was collected the anthropometrical measurements and the hydrostatical weighing and analyzed through of the average, pattern deviation, and throug the Constant Error (EC), using the statistical program SPSS 80. The results show that the mathematical models proposed by Lohman (1981) and Jackson and Pollock (1978) are those which obtained the smallest constant errors, independently of which model was utilized to the conversion of the corporal density to the fat percentual. In these inverse of this result, where are included the other mathematical models proposed, outstanding the Durnin and Womersley's model (1971), which presented the biggest constant error to the fat percentual and fat mass, load to an error of valuation when compared the pattern method. It was concluded that the mathematical models, proposed by Jackson and Pollock (1978) and Lohman (1981), presented themselves, as the best, indepently of the used equation to convert the corporal density in percentual of fat in the fractionalization of the corporal composition in professional athletes of foot-ball.
Keywords: Athlete; Foot-ball; Anthropometry.